2022
DOI: 10.1101/2022.01.02.474733
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Capsaicin potently blocks Salmonella typhimurium invasion of Vero cells

Abstract: As at 2021, the center for disease control (CDC) reported that Salmonella causes 1.2 million illness in the United States each year, with a mortality rate approaching 500 deaths per annum. Infants, the elderly, and persons with compromised immunity are the population with higher risk of mortality from this infection. At present there is no commercially available, safe and efficacious vaccine for the control and management of Salmonella typhimurium (S. typhimurium). More so, S. typhimurium has been shown to dev… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…As this facultative anaerobe continues to cause serious public health problems, the need to investigate Salmonella has received much scientific scrutiny [61][62][63][64]. In this study, we demonstrated the antibacterial activity of CBD against two relevant pathogenic bacteria, S. typhimurium and S. newington.…”
Section: Discussionmentioning
confidence: 85%
“…As this facultative anaerobe continues to cause serious public health problems, the need to investigate Salmonella has received much scientific scrutiny [61][62][63][64]. In this study, we demonstrated the antibacterial activity of CBD against two relevant pathogenic bacteria, S. typhimurium and S. newington.…”
Section: Discussionmentioning
confidence: 85%